Advanced Technologies in Digitizing Cultural Heritage Volume II - Akrivi Katifori; Angeliki Antoniou; Areti Damala; Paraskevi Raftopoulou (Applied Sciences)
The need to digitize cultural heritage is important and well documented [...]